Creativity in the acquisition of computational thinking. Issue 5 (18th August 2019) - Hershkovitz, Arnon; Sitman, Raquel; Israel-Fishelson, Rotem; Eguíluz, Andoni; Garaizar, Pablo; Guenaga, Mariluz
ABSTRACT: Many worldwide initiatives consider both creativity and computational thinking as crucial skills for future citizens, making them a priority for today's learners. We studied the associations between these two constructs among middle school students ( N  = 57), considering two types of creativity: a general creative thinking, and a specific computational creativity. We did so using learning analytics, specifically, by operationalizing a log-based assessment of computational creativity. We find some evidence for an association between Computational Creativity and Computational Thinking: Demonstrating originality in an early stage of the game is associated with succeeding in this stage relatively easily, however negatively associated with progressing farther in the game. We also find that Computational Creativity is better explained by a state- rather than a trait-model. No associations were found between Creative Thinking and Computational Thinking. Furthermore, we find some striking associations between the two measures of creativity.